2021
DOI: 10.3390/vetsci8030053
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Multicentric Study of Electrochemotherapy in the Treatment of Feline Nasal Planum Squamous Cell Carcinoma

Abstract: Feline squamous cell carcinoma (SCC) is currently treated with surgery, radiation therapy and electrochemotherapy (ECT). Both the efficacy and/or safety of ECT were evaluated as a sole therapy with bleomycin to treat feline nasal planum SCC (npSCC). Sixty-one cats were enrolled. Local treatment response was evaluated as complete remission (CR), partial remission (PR) or stable disease (SD). Recurrence rate (RR), disease-free interval (DFI) and progression free survival (PFS) were calculated. A six-point scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…We reserve RT for very large tumors when the risk of relapse with a single ECT session is high. Very large tumors can be challenging to treat with ECT, as areas may be left untreated unintentionally [40] . If large tumors are meant to be treated with ECT, a close follow-up is advisable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We reserve RT for very large tumors when the risk of relapse with a single ECT session is high. Very large tumors can be challenging to treat with ECT, as areas may be left untreated unintentionally [40] . If large tumors are meant to be treated with ECT, a close follow-up is advisable.…”
Section: Discussionmentioning
confidence: 99%
“…ECT may be used independently or in combination with surgery, especially when the surgery cannot provide clean margins. ECT may be used as a neoadjuvant, adjuvant, or concomitant therapy [37][38][39][40] . Some authors have reported an objective response rate of 97.3% when treating feline patients with nasal planum cSCC with minimum side effects [41] .…”
Section: Electrochemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“… 6 ECT has also been shown to have good safety and efficacy in treating feline squamous cell carcinoma of the nasal planum. 17 …”
Section: Discussionmentioning
confidence: 99%
“…6 ECT has also been shown to have good safety and efficacy in treating feline squamous cell carcinoma of the nasal planum. 17 There is currently minimal literature describing ECT treatment for feline nasal melanoma. One case report describes the use of ECT combined with calcium electroporation (CaEP) for the treatment of a cat with cutaneous malignant melanoma with regional metastasis; the affected animal had a cutaneous peripalpebral plaque lesion, with submandibular lymph node enlargement.…”
Section: Discussionmentioning
confidence: 99%